1994
DOI: 10.1136/bmj.309.6956.722
|View full text |Cite
|
Sign up to set email alerts
|

ABC of Breast Diseases : Symptoms Assessment and Guidelines for Referral

Abstract: Bathsheba bathing" by Rembrandt. The model was Rembrandt's mistress, and much discussion has surrounded the shadowing in her left breast and whether this represents an underlying malignancy. A breast lump, which may be painful, and breast pain constitute over 80% of the breast problems that require hospital referral, and breast problems constitute up to a quarter of the general surgical workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…Some reports have found no association with cancer in patients with serous, sero-sanguinous or coloured secretion [11]; others have found a higher malignancy rate with bloody ND while still others have reported no such findings [12,13].…”
Section: Introductionmentioning
confidence: 95%
“…Some reports have found no association with cancer in patients with serous, sero-sanguinous or coloured secretion [11]; others have found a higher malignancy rate with bloody ND while still others have reported no such findings [12,13].…”
Section: Introductionmentioning
confidence: 95%
“…Biopsy procedures also have morbidities like residual lump and persistent pain at scar site. 12 In our study, 33 cases of fibrocystic changes: majority (51.5%) were non-proliferative, followed by proliferative without atypia (45.5%) and only one case (3%) showed proliferation with atypia. Dupont et al reported that presence of proliferation and atypia had 1.9 and 5.3 times risk of developing cancer respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Triple assessment or TA (physical examination, mammography and FNA), when positive, has a diagnostic accuracy of almost 100%, 4 and for this reason, open biopsy is hardly ever indicated. If FNA is inconclusive, a core needle biopsy can often solve the problem and open surgical biopsy should be avoided and used only on rare occasions.…”
Section: Discussionmentioning
confidence: 99%